Studi In Vitro Temulawak (Curcuma xanthorrhiza) dan Kencur (Kaempferia galanga) sebagai Feed Additive Alami Terhadap Fermentabilitas dan Protozoa Rumen: Study of Fermentability and Rumen Protozoa from Javanese Turmeric (Curcuma xanthorrhiza) and Aromatic Ginger (Kaempferia galanga) as Natural Feed Additives - A Rosmalia; Evvyernie, Dwierra; D E Yolanda; D M Fassah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
This research investigated the potential of Javanese turmeric (Curcuma zanthorrhiza) and aromatic ginger (Kaempferia galanga) as natural feed additives in dairy cow diets, focusing on their effects on rumen fermentation characteristics and and protozoa population through an in vitro study. The study employed a randomized block design consisting of four treatments and three replicates, utilizing rumen fluid obtained from three fistulated Friesian Holstein bull dairy cows. The treatments were defined as follows: P0 = control diet; P1 = P0 + 10% Javanese turmeric; P2 = P0 + 10% aromatic ginger; P3 = P0 + 5% Javanese turmeric + 5% aromatic ginger. The parameters assessed included rumen pH, ammonia (NH3) concentration, total volatile fatty acids (VFA) concentration, and protozoa population. Data analysis was performed using analysis of variance (ANOVA), followed by Duncan’s multiple range test to identify significant differences (p<0.05). The results showed that none of the treatments significantly affected on the measured parameters (rumen pH, ammonia, VFA, and protozoa populations). The best results were observed in treatment P2 (10% aromatic ginger), which exhibited average values within the normal range across all parameters. The study concluded that dietary inclusion of Javanese turmeric and aromatic ginger, either alone or combined, did not disrupt rumen fermentation balance.